1980
DOI: 10.1085/jgp.75.5.553
|View full text |Cite
|
Sign up to set email alerts
|

Conductive properties of the proximal tubule in Necturus kidney.

Abstract: The electrical properties of the proximal tubule of the in vivoNecturus kidney were investigated by injecting current (as rectangular waves) into the lumen or into the epithelium of single tubules and by studying the resulting changes of transepithelial (VL) and/or cell membrane potential (V c) at various distances from the source. In some experiments paired measurements of VL and Vc were performed at two abscissas x and x'. The luminal length constant of about 1,030 pm was shown to provide a good estimate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Although subject to similar variation in the physiological status of the kidney and in the experimental technique, reported values of 2 C in free-flow tubules are less variable than reported values of 2 t. For example, Windhager et al [22] and Anagnostopolous and Velu [2] reported values for 2~r of 200 ~tm and Anagnostopolous et al [1] values of 2 c from 214 to 250~tm for the Necturus proximal tubule and a value of 248 gm is reported in the present study.…”
Section: Apical and Basolateral Ceil Membrane Resistances In Parallelsupporting
confidence: 60%
See 1 more Smart Citation
“…Although subject to similar variation in the physiological status of the kidney and in the experimental technique, reported values of 2 C in free-flow tubules are less variable than reported values of 2 t. For example, Windhager et al [22] and Anagnostopolous and Velu [2] reported values for 2~r of 200 ~tm and Anagnostopolous et al [1] values of 2 c from 214 to 250~tm for the Necturus proximal tubule and a value of 248 gm is reported in the present study.…”
Section: Apical and Basolateral Ceil Membrane Resistances In Parallelsupporting
confidence: 60%
“…Spatial decay of current in one cable is unaffected by the other cable. Recently, Anagnostopolous et al [1] have suggested that the measurements of cellular cable properties in the Necturus proximal tubule by means of intracellular current injection as shown in method d of this paper may be inaccurate because of a significant cable-to-cable interaction or "cross talk. "…”
Section: Apical and Basolateral Ceil Membrane Resistances In Parallelmentioning
confidence: 91%
“…Therefore, special care was taken to reduce the influence of "crosstalk" on the obtained resistance values. As demonstrated in the mammalian cortical thick ascending limb of Henle's loop [10] some length dependence of the apparent cell membrane resistance ratio has been observed resembling "crosstalk" as also discussed recently for the amphibian proximal tubule [1,13,16]. Furthermore, it is known that the evaluation of the length constant of the cell cable at distances of more than 700/~m from the current source Assuming a K+-selective luminal cell membrane, Elu and extraceUular K + are used to estimate intracellular potassium.…”
Section: Critique Of the Methodssupporting
confidence: 54%
“…cm 2 [14]. However, they are less than those of Anagnostopoulos et al [4] who report values of 420 ft. cm 2 for Rte. The Rte of Anagnostopoulos et al is in the range of the resistances found across the late proximal tubule of Necturus which range from 429 [11] to 641 fl-cm 2 [14].…”
Section: Effect Of Low Cl-on Transepitheliai Resistancementioning
confidence: 64%